SWOT Analysis Based on A Marketing Mix to Optimize Marketing Strategy Al-Qur'an Learning Services - Ach. Saifullah; Prim Masrokan M.; Agus Eko Sujianto (STAI Terpadu Yogyakarta, 2024)
This study aims to describe how SWOT analysis based on the marketing mix is used in Qur'anic instruction at MI Islamiyah Jombang. This research answers: 1) How does SWOT analysis based on marketing mix place the quadrant of Al-Qur'an learning? 2) How can the SWOT analysis results based on the marketing mix optimize the marketing strategy of Al-Qur'an Learning? The results showed that TPQ Al-Ichsany became part of the business unit strategy managed by MI Islamiyah Jombang to serve Qur'anic learning. The analysis of the total IFAS score for strengths is 3.025, and for weaknesses is 1.122. The EFAS score for opportunities is 2,392; for threats, it is 1,012. The position of Al-Qur'an learning at MI Islamiyah Jombang is in Quadrant I (+,+). Al-Qur'an learning is in excellent and steady condition. A marketing services strategy was used to support the aggressive growth policy. Intensive strategies through market penetration and market development are strategies to expand, enlarge growth, and seize maximum opportunities for the continuous progress of Qur'anic education.